2011
DOI: 10.1177/0898264311422598
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Medications in Predicting Activity Restriction Due to a Fear of Falling

Abstract: Objectives: To examine the role of medication use and other factors in predicting activity restriction due to a fear of falling (AR/FF). Methods: Older adults were assessed twice with the interRAI Community Health Assessment and the Berg Balance Scale (BBS). The main outcome was limiting going outdoors due to an AR/FF. Medications were recorded by trained assessors. Results: Participants (n = 441) had a mean age of 80.3 (SD = 7.1) years, most were aged 65+ (96.8%) and 29.3% reported activity restriction. Takin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…[17][18][19][20] As such, balance and gait features may not show a relationship to the rate of falls over time if these same features also are found in individuals with diminished physical activity, as has been observed previously. [21][22][23][24][25] The healthiest way to avoid falls is to fall less per step taken and not to simply restrict activity, suggesting that it is important to identify and address factors associated with a higher rate of falls per step in addition to factors associated with a higher rate of falls per year. 26 This is particularly relevant when analyzing gait features that predispose individuals to falling only when the individual is walking.…”
mentioning
confidence: 99%
“…[17][18][19][20] As such, balance and gait features may not show a relationship to the rate of falls over time if these same features also are found in individuals with diminished physical activity, as has been observed previously. [21][22][23][24][25] The healthiest way to avoid falls is to fall less per step taken and not to simply restrict activity, suggesting that it is important to identify and address factors associated with a higher rate of falls per step in addition to factors associated with a higher rate of falls per year. 26 This is particularly relevant when analyzing gait features that predispose individuals to falling only when the individual is walking.…”
mentioning
confidence: 99%
“…A study conducted by Carvalho, Pinto, and Mota (2007) verified that individuals with better body balance are less afraid of falling. Guthrie et al (2011) also found that balance, assessed by means of BERG balance scale, is associated with fear of falling. The authors suggest, additionally, that balance can be a more important variable to fear of falling than consumption of medicines, for instance, which is a variable commonly linked in the literature to concern with falls (Guthrie et al, 2011).…”
Section: Resultsmentioning
confidence: 98%
“…The study included 441 subjects whose average lifespan was 80.7 years. Of the total number, 29.3% of subjects reported having limitations to daily living tasks due to fear of falling (20). Our study did not explicitly contain the question of whether there were restrictions on daily living tasks due to fear of falling, but we had a question as to whether the subjects avoided going out due to the fear of falling.…”
Section: Discussionmentioning
confidence: 98%